The Mind aging - Hanser, David; Hemingway, John (The Mind series, 1988)
What happens to the brain and mind during the aging processn Why do some people age and still retain full mental capacity while others lose agility of the mindn This enlightening episode of the mind questions many of the long-held stereotypes about aging. The diseases of aging, stroke, Alzheimers and Parkinsons disease are analyzed with emphasis on the fact that they are totally distinct from the normal aging process. Finally, this episode closes with a look at the phenomenon most commonly associated with older minds : Wisdom.